(untitled) (Comprehensive Journal of Science, 2025)
The study aimed to identify the challenges of implementing Islamic banking in specialized banks. To achieve the study’s objectives, the descriptive-analytical approach was adopted to survey the opinions of a sample consisting of 59 employees. After distributing the questionnaire, 54 valid responses were retrieved and analyzed using SPSS software. The general results of the study indicated that there are significant challenges hindering the implementation of Islamic banking in specialized banks. Finally, the study concluded with a set of recommendations and proposed solutions, the most important of which is the necessity for banks to provide Sharia-based training and education for their employees, ensuring their full understanding of the principles of Islamic financial transactions. The study also recommended that banks should adapt all current laws and banking transactions to comply with Islamic Sharia.